Pancreatic stellate cells promote proliferation and invasiveness of human pancreatic cancer cells via galectin-3 - Jiang, Hai-Biao; Xu, Ming; Wang, Xing-Peng (World journal of gastroenterology : WJG, 2008)
AIM： To investigate the role of pancreatic stellate cells （PSCs） and galectin-3 （GAL-3） in the proliferation and infiltration of pancreatic cancer cell line SW1990. METHODS： Human pancreatic cancer cell line SW1990 and PSCs were cultured in vitro. Supernatant fluid of cultured PSCs and SW1990 cells was collected. Expression of GAL-3 in SW1990 cells and PSCs was detected by ELISA, RT-PCR and Western blotting. Proliferation of cultured PSCs and SW1990 cells was measured by 3-（4, 5-methylthiazol-2-yl）-2, 5-diphenyltetrazolium bromide （MTT） assay and flow cytometry. Infiltration of SW1990 cells was detected by a cell infiltration kit. RESULTS： SW1990 cells expressed GAL-3 and this was up-regulated by the supernatant fluid of cultured PSCs. PSCs did not express GAL-3. SW1990 cells stimulated proliferation of PSC,s via GAL-3. GAL-3 antibody inhibited SW1990 cell proliferation, while the supernatant fluid of PSCs stimulated proliferation of SW1990 cells through interaction with GAL-3 protein. The supernatant fluid of PSCs enhanced the invasiveness of SW1990 cells through interaction with GAL-3. CONCLUSION： GAL-3 and PSCs were involved in the proliferation and infiltration process of pancreatic cancer cells.